Solid-state battery, separator, electrode and manufacturing method
By using sintered electrochemically active materials, inorganic solid particulate electrolytes and low melting point electrolytes in solid-state lithium-based batteries, combined with low-temperature sol gel process and melt quenching method, the problems of high cost, low capacity and high impedance in the battery manufacturing process are solved, and high rate performance and effective transmission of lithium ions are achieved.
Patent Information
- Application Number
- CN202210195421.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-09-22
- Filing Date
- 2016-12-21
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2036-12-21
AI Technical Summary
The existing solid-state lithium-based batteries have problems of high cost, low capacity and high impedance in the manufacturing process, and it is difficult to achieve stable lithium ion transmission.
The composite electrode structure consisting of sintered electrochemically active materials, inorganic solid particulate electrolytes with high conductivity and low melting point solid inorganic electrolytes were prepared by a low-temperature sol gel process and a melt quenching method.
It realizes high-rate performance and effective transmission of lithium ions, reduces the manufacturing cost of the battery, and improves the stability and capacity of the battery.
Smart Images

Figure CN114551990B_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese invention patent application No. 2016800753183, which was filed on December 21, 2016 and whose invention name is “Solid-state battery, separator, electrode and manufacturing method”.
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims priority to U.S. Provisional Patent Application No. 62 / 270,269 filed on December 21, 2015, U.S. Provisional Patent Application No. 62 / 315,760 filed on March 31, 2016, and U.S. Provisional Patent Application No. 62 / 398,030 filed on September 22, 2016, the disclosures of which are incorporated herein by reference in their entirety. Background of the Invention
[0004] Solid-state lithium batteries were developed by Duracell in the 1970s and were commercially available in the 1980s, but are no longer produced. These batteries consist of a lithium metal anode, a dispersed phase electrolyte of lithium iodide and Al2O3, and a metal salt as the cathode. The Li / LiI(Al2O3) / metal salt structure is a true solid-state battery, but these batteries are not rechargeable.
[0005] Due to the unstable interfaces and passivation reactions formed between organic electrolyte materials such as liquid and solid polymer electrolytes, there has long been an effort to develop rechargeable solid-state lithium-based batteries using inorganic solid electrolyte materials. In the early 1990s, the Oak Ridge National Laboratory developed a second all-solid-state battery. These batteries consist of thin films of cathode, inorganic electrolyte, and anode materials deposited on a ceramic substrate using vacuum deposition techniques (including RF sputtering for cathode and electrolyte and vacuum evaporation of Li metal anode). The total thickness of the battery is typically less than 10 μm: the cathode has a thickness of less than 4 μm, the solid electrolyte has a thickness of about 2 μm (just enough to provide electrical isolation of the cathode and anode), and the Li anode has a thickness of about 2 μm. The transport properties of these batteries are very good due to the strong chemical bonding provided by physical vapor deposition techniques (including within each layer of the battery and between layers). Although the solid electrolyte LiPON has a thickness of only 2×10 -6 S / cm -1 The conductivity of the 2μm layer is 50 times lower than that of the LiI(Al2O3) solid electrolyte used in previous Duracell batteries, and the impedance of the 2μm thin layer is very small, allowing very high rate performance. However, batteries based on this technology are very expensive to manufacture, are very small, and have very low capacity.
[0006] Solid-state batteries have attracted much attention due to their potentially attractive performance characteristics, including long shelf life, long-term stable power performance, no gassing, a wide operating temperature range (-40°C to 170°C for pure lithium anodes and up to and exceeding 300°C using active composite anodes) and high volumetric energy density (up to 2000Wh / L). They are particularly suitable for applications requiring long life under low consumption or open circuit conditions.
[0007] Currently, lithium-ion battery chemistry using liquid electrolytes provides the best-known performance and is becoming the most widely used of all battery chemistries. Lithium-ion batteries consist of a thick (~100 μm) porous composite cathode that is cast on a thin (~10 μm) Al foil current collector. Due to the high capacity and good cycle life of LiCoO2, the composite cathode usually contains LiCoO2 as the active material and carbon black that provides conductivity throughout the layer. In order to improve battery performance, many active cathode materials have been and are being studied. Some of these materials have been implemented in batteries, including lithium nickel cobalt manganese oxide. A thin polymer separator provides electrical isolation between the cathode and the carbon-based anode. The anode inserts Li during the charging cycle. The battery is immersed in a liquid electrolyte, which provides very high conductivity for lithium ion transport between the cathode and anode during charging and discharging. Since the separator and the composite cathode and anode are all porous, the liquid electrolyte is absorbed and filled into these structures, providing excellent surface contact with the LiCoO2 active material and allowing Li ions to be rapidly transported throughout the battery with minimal impedance.
[0008] The liquid electrolyte itself consists of a Li salt (e.g., LiPF6) in a solvent blend that typically includes ethylene carbonate and other linear carbonates such as dimethyl carbonate. Despite improvements in energy density and cycle life, batteries containing liquid electrolytes still have several potential problems. For example, liquid electrolytes are generally volatile and are subject to pressure buildup, explosion, and fire under high charge rates, high discharge rates, and / or internal short circuit conditions. In addition, high-rate charging can cause dendritic lithium growth on the anode surface. The resulting dendrites can penetrate the separator and short-circuit internally in the battery. In addition, the self-discharge and efficiency of the battery are limited by side reactions and corrosion of the cathode by the liquid electrolyte. In addition, liquid electrolytes can also be dangerous if the battery overheats due to overvoltage or short circuit conditions, creating another potential fire or explosion hazard.
[0009] To address the safety and reliability issues of lithium-based batteries using liquid electrolytes and to achieve high energy density, solid-state batteries that employ high-capacity lithium intercalation compounds are being developed. Past attempts to build such all-solid-state batteries have been limited by the need to bond the materials together to facilitate efficient lithium ion transport across the interface. This bonding approach has been attempted by sintering at high temperatures, such as 800°C and higher. However, the cathode and electrolyte materials can react with each other at such sintering temperatures, resulting in a high impedance interface and an ineffective battery.
[0010] To avoid the parasitic reaction problems associated with high-temperature sintering, all solid-state batteries have been developed using low-temperature sol-gel processes. These all-solid-state batteries consist of active battery cathode materials (e.g., LiNiMnCoO2, LiCoO2, LiMn2O4, Li4Ti5O 12 or similar materials), a conductive material (e.g., carbon black) and a lithium ion conductive glass electrolyte material (e.g., Li ion conductive glass electrolyte material) 3x La 2 / 3-x TiO3(x=0.11)(LLTO) or Li7La3Zr2O 12 When the precursor gels and then solidifies at low temperature, the precursor is converted into a solid lithium-ion conductive glass electrolyte.
[0011] When constructing solid-state batteries using a low-temperature sol-gel method, the cathode can be formed by mixing lithium active materials, conductive materials, and liquid sol-gel precursors to form a uniform mixture or paste. The cathode can be formed as a thick pellet or thin cast piece containing the cathode component mixture. The cathode is held together by an ion-conducting glass electrolyte matrix formed by gelling and curing the sol-gelled precursor solution. The curing temperature of the gelled precursor is in the range of 300°C, so parasitic reactions are avoided.
[0012] However, the use of sol-gel methods to produce glass electrolytes as binders to make battery electrodes requires proper gelation, drying and curing of the precursors. The gelation of LLTO and LLZO precursors is a hygroscopic process. Water must diffuse into the cathode structure through the tortuous paths formed by the densely packed cathode powder materials so that the cathode materials are properly gelled everywhere. Drying of the precursors after gelation can be time-consuming because the solvents and alcohols must diffuse through the gel electrolyte within the tortuous dense electrode powder structure.
[0013] The all-solid-state primary cell developed by Duracell and described above shows very high energy density up to 1000Wh / L and excellent performance in terms of safety, stability and low self-discharge. However, due to the pressed powder structure and the requirement for a thick electrolyte separation layer, the cell impedance is very high, severely limiting the discharge rate of the cell. This type of cell is also limited in application because the electrochemical window is limited to less than 3 volts due to the oxidation of iodide ions in the electrolyte above about 3 volts. In addition, a stable rechargeable version of this cell has never been developed.
[0014] As detailed above, the all-solid-state thin-film battery developed by Oak Ridge National Laboratory solves many problems associated with lithium-ion technology, but also has limitations. The vacuum deposition equipment required to manufacture the battery is very expensive and the deposition rate is slow, resulting in very high manufacturing costs. Moreover, in order to take advantage of the high energy density and power density provided by the use of thin films, it is necessary to deposit the film on a substrate that is thinner and lighter than the battery layer itself, so that the battery layer constitutes a significant part of the volume and weight of the battery compared to the inert substrate and packaging components. Ideally, one would simply use a thicker battery electrode layer so that the substrate accounts for a less important proportion of the battery volume; however, it is not practical to increase the electrode thickness by more than a few microns. The low lithium diffusion rate combined with the thick electrode layer results in an impractical battery with a low charge and discharge rate. Therefore, the film must be deposited on a very thin substrate (<10μm) or multiple batteries must be built on a single substrate, which leads to the problem of maintaining low interfacial impedance with the electrolyte during the high temperature annealing required after the cathode material is deposited.
[0015] Conductivity in the range of 10 -3 S / cm range. However, the use of such materials as solid electrolytes in all-solid-state batteries is limited, in part, due to the high interfacial impedance caused by the high temperature sintering process used to form the bond between the electrolyte and the active cathode material. While the bond is required to enable lithium ion conduction between the materials, the interatomic migration during the sintering process leads to very high interfacial impedance and very limited functionality of the resulting battery.
[0016] Although solid-state batteries have been made with a homogenous mixture of electrolyte and active material powders combined using low-temperature processing to produce low interfacial impedance, improved charge / discharge rate capabilities, obtaining the full capacity of thicker cathodes remains very limited. Figure 1 The various layers of a solid state battery constructed using prior art methods are shown, including cathode current collector 8, cathode 6, electrolyte separator 4, and anode layer 2. In the expanded view, solid electrolyte particles 12 embedded within cathode active material 10 are shown.
[0017] The cathode 6 is constructed with enough solid electrolyte material 12 to achieve permeation so that there is a network of particles in contact with each other to achieve ion conduction continuity. The standard construction procedure for the cathode is to mix the constituent cathode powder materials until the electrolyte particles are relatively evenly distributed. A relatively even but random distribution is maintained during the construction of the battery cell so that Figure 1 The configuration shown represents a complete battery according to the prior art. It illustrates some of the challenges faced in building solid-state batteries, especially those with relatively thick cathodes. Due to the random mixing process, some percentages of electrolyte materials, particles and particle groups will naturally be surrounded by active cathode materials and thus isolated from the electrolyte network, as shown by particles 14. These isolated particles cannot participate in transporting lithium ions from the separator to the cathode. For example, consider a lithium ion 22 that is conducted through the electrolyte layer 4. It continues the conduction path through the electrolyte particles 24. It receives electrons 18 or 20 and transforms into active material 10. Upon receiving the electron, it returns to its full lithium state 26 and is embedded in the cathode material 10 by diffusion. Once in the full lithium state, the atom cannot enter the electrolyte particles 25, releases the electron 28, and conducts the electron via a parallel path 28, so that it is reconstructed as lithium at 30, thereby conducting deep within the cathode. Once inserted into the active cathode material as lithium, its transport within the cathode will be carried out by diffusion, which is too slow for most applications.
[0018] Another problem is the limited cross-sectional area where the electrolyte particles connect to each other as shown at 15. These interfacial limited areas act like conduction blocking points. Due to the small contact area between the particles, they tend to increase the impedance.
[0019] Yet another problem is represented by the network of particles 16. Ideally, lithium ions 17 enter the network and conduct through a series of interconnected particles to insert into the active material 10 at location 19. This is a tortuous path, made worse by the fact that the ions must conduct in the opposite direction to the direction of the electron charge field to insert at 19. Given the positive charge of the lithium ion, it is not clear that this will occur.
[0020] The net effect is that solid-state batteries with a cathode having a conductive electrolyte and random distribution of active particles show limited performance. Therefore, there remains a need for a solid-state battery structure and production process that provides high rate performance and efficient transport of lithium within the structure of the internal electrode. Summary of the invention
[0021] The present invention relates to a solid-state battery comprising a cathode, a separator and an anode, wherein at least one of the cathode and the anode comprises a sintered electrochemically active material, a first inorganic solid granular electrolyte having a high electrical conductivity and a first low-melting point solid inorganic electrolyte, wherein the first inorganic solid granular electrolyte has a particle size of about 100 nm to about 100 microns, and wherein the first low-melting point solid inorganic electrolyte comprises a doped metal oxide containing at least one of boron and carbon.
[0022] The present invention also relates to an amorphous or glass-ceramic lithium ion conducting inorganic electrolyte comprising a doped metal oxide containing at least one of boron and carbon.
[0023] Furthermore, the present invention relates to a method for producing an amorphous or glass-ceramic inorganic electrolyte comprising a doped metal oxide containing at least one of carbon and boron, the method comprising forming a coating of a powder of the doped metal oxide on a substrate, heating the coated substrate to liquefy the powder, and quenching the coated substrate at a temperature below the melting point of the powder to form an amorphous or glass-ceramic electrolyte.
[0024] A solid-state battery comprising a cathode, a separator and an anode, wherein at least one of the cathode and the anode comprises a sintered electrochemically active material, a first inorganic solid granular electrolyte having a high ionic conductivity and a first low-melting point solid inorganic electrolyte, wherein the first inorganic solid granular electrolyte has a particle size of about 100 nm to about 1 mm, and wherein the first low-melting point solid inorganic electrolyte comprises a doped metal oxide containing at least one of boron and carbon.
[0025] In another preferred example, the first low melting point solid inorganic electrolyte extends through the pores of the cathode and / or the anode.
[0026] In another preferred embodiment, the doped metal oxide is doped lithium oxide.
[0027] In another preferred embodiment, the doped metal oxide is doped with about 0.1 to about 20 atomic percent of a dopant element or compound.
[0028] In another preferred embodiment, the doped metal oxide is a lithium metal oxide doped with at least one element or compound selected from the group consisting of silicon, fluorine, germanium, sulfur, lithium fluoride, silicon dioxide, lithium metaborate and lithium orthoborate.
[0029] In another preferred embodiment, the first low melting point solid inorganic electrolyte is at least one material selected from the group consisting of: lithium carbonate doped with lithium metaborate, silicon-doped lithium tetraborate, lithium metaborate doped with lithium fluoride, silicon-doped lithium tetraborate, lithium carbonate doped with lithium orthoborate (Li3BO3-Li2CO3), lithium orthoborate doped with lithium carbonate (Li2CO3-Li3BO3), silicon dioxide-doped Li3BO3-Li2CO3, lithium fluoride-doped Li3BO3-Li2CO3, fluorine-doped Li3BO3-Li2CO3, sulfur-doped Li3 BO3-Li2CO3, silicon-doped Li3BO3-Li2CO3, fluorine and silicon-doped Li3BO3-Li2CO3, germanium-doped Li3BO3-Li2CO3, silicon dioxide-doped Li2CO3-Li3BO3, lithium fluoride-doped Li2CO3-Li3BO3, fluorine-doped Li2CO3-Li3BO3, sulfur-doped Li2CO3-Li3BO3, silicon-doped Li2CO3-Li3BO3, fluorine and silicon-doped Li2CO3-Li3BO3 and germanium-doped Li2CO3-Li3BO3.
[0030] In another preferred embodiment, the first low melting point solid inorganic electrolyte has a general formula N v N′ w N″ x N″′ y N″″ z ,in,
[0031] N represents at least one element selected from Group IA of the periodic table,
[0032] N' represents at least one element selected from Group IVA of the periodic table,
[0033] N" represents at least one element selected from Group IIIA of the Periodic Table,
[0034] N'" represents at least one element selected from Group VIA of the Periodic Table, and
[0035] N"" represents at least one dopant selected from Groups IA to VIIA of the periodic table and transition metals, and
[0036] wherein v, w, x, y and z are each zero or a positive number, including various combinations of integers and fractions or decimals, provided that the electrolyte contains oxygen and at least one of carbon and boron.
[0037] In another preferred embodiment, N represents lithium, N' represents carbon, N" represents boron, N"' represents oxygen, and N"" represents silicon.
[0038] In another preferred embodiment, at least one of the cathode and the electrode further comprises an electronically conductive material.
[0039] In another preferred example, the separator includes a second inorganic solid particulate electrolyte having high ionic conductivity, wherein the second inorganic solid particulate electrolyte has a particle size of about 100 nm to about 100 microns.
[0040] In another preferred example, the separator further comprises a second low melting point solid inorganic electrolyte.
[0041] In another preferred example, the second low-melting-point solid inorganic electrolyte comprises a doped metal oxide containing at least one of boron and carbon.
[0042] In another preferred embodiment, the second low melting point solid inorganic electrolyte is at least one material selected from the group consisting of: lithium carbonate doped with lithium metaborate, silicon-doped lithium tetraborate, lithium metaborate doped with lithium fluoride, silicon-doped lithium tetraborate, lithium carbonate doped with lithium orthoborate (Li3BO3-Li2CO3), lithium carbonate doped with lithium orthoborate (Li2CO3-Li3BO 3) , silicon dioxide doped Li3BO3-Li2CO3, lithium fluoride doped Li3BO3-Li2CO3, fluorine doped Li3BO3-Li2CO3, sulfur doped Li3BO3-Li2CO3, silicon doped Li3BO3-Li2CO3, fluorine and silicon doped Li3BO3-Li2CO3, germanium doped Li3BO3-Li2CO3, silicon dioxide doped Li2CO3-Li3BO3, lithium fluoride doped Li2CO3-Li3BO3, fluorine doped Li2CO3-Li3BO3, sulfur doped Li2CO3-Li3BO3, silicon doped Li2CO3-Li3BO3, fluorine and silicon doped Li2CO3-Li3BO3 and germanium doped Li2CO3-Li3BO3.
[0043] In another preferred embodiment, the second low melting point solid inorganic electrolyte has a general formula N v N′ w N″ x N″′ y N″″ z ,in,
[0044] N represents at least one element selected from Group IA of the periodic table,
[0045] N' represents at least one element selected from Group IVA of the periodic table,
[0046] N" represents at least one element selected from Group IIIA of the Periodic Table,
[0047] N'" represents at least one element selected from Group VIA of the Periodic Table, and
[0048] N"" represents at least one dopant selected from Groups IA to VIIA of the Periodic Table and transition metals, and
[0049] where v, w, x, y, and z are each zero or a positive number, including various combinations of integers and fractions or decimals.
[0050] In another preferred example, the separator is amorphous or glass-crystalline.
[0051] In another preferred example, at least one of the cathode and the anode is amorphous or glass-crystalline.
[0052] In another preferred example, the separator has a first side and a second side, the cathode is arranged on the first side of the separator, and the anode is arranged on the second side of the separator, and the granular electrolyte particles contained in the cathode and / or the anode extend into the separator.
[0053] In another preferred example, the cathode contains the first inorganic solid particulate electrolyte, and wherein the diameter of the particulate electrolyte particles accounts for about 60 to 80% of the thickness of the cathode.
[0054] BRIEF DESCRIPTION OF THE SEVERAL VIEWS OF THE DRAWINGS
[0055] The foregoing summary and the following detailed description of the invention will be better understood when read in conjunction with the accompanying drawings. For the purpose of illustrating the invention, there are shown in the accompanying drawings presently preferred embodiments. However, it should be understood that the invention is not limited to the precise arrangements and instrumentalities shown.
[0056] In the attached picture:
[0057] Figure 1 is a schematic diagram of a prior art solid-state battery having a composite cathode;
[0058] Figure 2 is a schematic diagram of a cathode cast onto a current collector substrate according to one embodiment of the present invention;
[0059] Figure 3 depicts large particles of electrolyte distributed across a surface of a solid cathode according to another embodiment of the present invention;
[0060] Figure 4 is a schematic diagram of a composite solid-state cathode according to another embodiment of the present invention, wherein large particles of electrolyte are embedded within the cathode surface, the cathode comprising particles of active cathode material bound together by a solid electrolyte;
[0061] Figure 5depicts an electrolyte separator coated on top of a composite cathode having large electrolyte particles embedded in the cathode surface according to another embodiment of the present invention;
[0062] Figure 6 is a schematic diagram showing a cross-sectional view and an expanded view of a composite cathode having large electrolyte particles embedded in the cathode surface according to another embodiment of the present invention;
[0063] Figure 7 is a schematic diagram showing a cross-section and an expanded three-dimensional view of a composite cathode having large electrolyte particles embedded in the cathode surface according to another embodiment of the present invention;
[0064] Figure 8a and 8b is an electrochemical impedance spectroscopy (EIS) spectrum of a highly conductive solid electrolyte according to one embodiment of the present invention;
[0065] Fig. 9 is an electrochemical impedance spectroscopy (EIS) spectrum of hot-pressed and melted boron-doped lithium carbonate particles (Li3BO3:Li2CO3) and melted LiF-doped Li3BO3:Li2CO3 according to another embodiment of the present invention;
[0066] Fig.10 is a graph of charge / discharge cycle data for a battery without large solid electrolyte particles embedded in the cathode according to one embodiment of the present invention.
[0067] Fig.11 are the electrochemical impedance spectroscopy (EIS) spectra of cells with and without large solid electrolyte particles embedded in the cathode;
[0068] Fig.12 is a graph of charge / discharge cycle data for a battery having large solid electrolyte particles embedded in a cathode according to one embodiment of the present invention; and
[0069] Fig.13 Graph of charge / discharge cycle data for cells having cathodes using NCM and solid electrolytes (nanoscale and / or large particle size) with and without Li3BO3-Li2CO3 sintering aids. DETAILED DESCRIPTION OF THE INVENTION
[0070] The present invention relates in part to an all-solid-state battery having a thick lithium active electrode relative to the thickness of other components. The battery has a high "C" rate performance, where the "C" rate is defined as the ampere-hour capacity of the battery divided by the discharge current. Therefore, the present invention solves the need in the art for improving lithium ion migration within solid-state battery electrodes by providing a heterogeneous mixture of electrode active materials and inorganic solid electrolyte materials. The inorganic solid electrolyte, preferably constructed as relatively large particles, extends a considerable distance into the electrode, providing a non-tortuous ion conduction path. For ion conduction continuity, the particles extend to the electrode surface and are bonded to the electrolyte separator layer. Such a configuration solves the need for a reduced tortuous conduction path, elimination of conduction blockage points, and an effective voltage field gradient to promote or facilitate the migration of ions through the electrolyte deep into the electrode. The present invention further provides a cost-effective structure of a continuous electrolyte extending into the cathode. The desired structure can be constructed by 3D printing a raw ceramic material containing electrolyte and active material features or more preferably by slurry casting of a raw ceramic tape having target features and particle size distribution.
[0071] More specifically, the present invention relates to solid-state primary batteries, solid-state rechargeable (secondary) batteries and components thereof. The solid-state battery according to the present invention has a composite electrode comprising a lithium active material, an inorganic lithium ion conductive electrolyte with a relatively high melting point and optionally a low melting point inorganic electrolyte material as a sintering aid and / or binder. The composite electrode may also include an electronic conductive additive material. For the purposes of this disclosure, the term "inorganic" may be understood as a material comprising a metal oxide-based glass or ceramic material. These materials preferably contain carbon but do not contain hydrogen. Each battery component will be described in more detail below.
[0072] Solid electrolyte-electrode composites
[0073] The solid electrolyte-electrode composite according to an embodiment of the present invention is also referred to herein as an "inorganic composite electrode" or simply a "composite electrode", and includes a composite cathode and a composite anode. For the purposes of this disclosure, unless otherwise specified, the terms "anode", "cathode" and "electrode" are used interchangeably.
[0074] The composite electrode according to the present invention comprises a sintered electrochemically active material and an inorganic solid particulate electrolyte having a relatively high melting point and high lithium ion conductivity. In a preferred embodiment, the composite electrode further comprises an inorganic solid electrolyte having a relatively low melting temperature.
[0075] Preferably, the active material is present in the composite electrode in an amount of about 50-90% by volume. The total amount of electrolyte material in the composite electrode is preferably about 50-10% by volume relative to the total electrode volume. If present, the percentage of low melting point electrolyte is preferably up to about 10% by volume when used as a sintering aid, and the percentage of low melting point electrolyte is preferably 5 to 50% by volume when used as a binder, relative to the total volume of the electrode.
[0076] When the composite electrode contains only active materials and a high melting point electrolyte, in a preferred embodiment, the components are sintered in a structured geometry that provides a non-tortuous electrolyte conductive path deep into the electrode. In other words, as described in more detail below, sintering involves heating just high enough to cause the particles to aggregate together and cause the particles of the electrolyte to embed within the electrode. Thus, most, if not all, of the electrode components are close to large particles.
[0077] The term "sintering" does not refer to a high temperature process, but rather to a process in which the particles fuse together without liquefying them. Sintering is performed at relatively low temperatures, such as between 750°C and 900°C, so that the electrode remains porous, but this results in the formation of good electronic conductive pathways. This lower temperature sintering process avoids the problems associated with high temperature sintering, such as parasitic reactions and atomic diffusion and migration, which can lead to high interfacial impedance between the lithium active material and the lithium electrolyte material.
[0078] In a preferred embodiment, the composite cathode contains a second relatively low melting point inorganic solid electrolyte, which will be described in more detail below. This electrolyte, which melts at about 300°C to 850°C, more preferably about 400°C to about 700°C, generally has a relatively low ionic conductivity. The second electrolyte is included in the sintered electrode in molten form to fill the pores of the electrode after sintering. As the melt cools and solidifies, it provides improved ion-conductive coupling between the active electrode material and the ion-conductive electrolyte, and further acts as a binder, improving the mechanical integrity of the cathode structure.
[0079] A second low melting point solid inorganic electrolyte may also be included in the composite electrode as a sintering aid to help sinter the electrode active material and the lithium ion conductive electrolyte together. The sintering aid reduces the temperature required to fuse the particles together. The sintering of the solid electrolyte and the electrode active material preferably results in a structured geometry that provides a non-tortuous electrolyte conductive path deep into the electrode.
[0080] By adding a low melting temperature sintering aid, the cathode can be formed at a lower temperature than without a sintering aid (about 750°C to about 950°C), for example between 400°C and 700°C, to form a good electronic conductive path. A denser cathode structure is obtained in this way. That is, the active material is cast and rolled with a lower percentage of a low melting temperature electrolyte so that the melting of the low melting temperature electrolyte provides the initial bonding of the cathode structure while leaving less void structure. As described above, in addition to using a second electrolyte as a sintering aid, it can also be inserted into the sintered electrode in a molten form to fill the pores of the electrode after sintering. Therefore, the second electrolyte can be included in the composite electrode at two different points in the manufacturing process to play two different roles or functions.
[0081] Each electrolyte in the composite electrode has a different function. Specifically, the high ionic conductivity electrolyte component dispersed within the electrode provides a low impedance to conduct lithium ions throughout the structure of the electrode, thereby providing a battery with high charge and discharge rate performance. The low melting temperature electrolyte primarily forms a thin interface layer between the component particles to minimize the overall ionic impedance of the electrode, reduce the bonding temperature, prevent undesirable parasitic reactions for initial bonding, and subsequently act as a binder during infiltration. As mentioned above, the low melting point electrolyte also acts as a sintering aid.
[0082] Thus, the different functional roles of the two electrolytes enable the construction of relatively thick low impedance electrodes. If the electrode has a separate structure such as a wafer or a particle, the current collector (aluminum, nickel, copper or similar metal) can be sputtered, evaporated or hot pressed onto the composite electrode as a coating to provide electrical contact. Alternatively, the electrode can be deposited or bonded to a metal foil. The composite electrode according to the present invention exhibits a high packing density of about 70 to 97%. In a preferred embodiment, the composite electrode according to the present invention is amorphous or glass-ceramic.
[0083] Electrochemically active materials
[0084] The electrochemically active material is preferably inorganic, and more preferably lithium-based, such as, but not limited to, lithium nickel cobalt manganese oxide (NCM), lithium titanium oxide (LTO), lithium nickel oxide (LNO), lithium cobalt oxide (LCO), or lithium manganese oxide (LMO); most preferably NCM. Other lithium-based electrochemically active materials known in the art or to be developed are also within the scope of the present invention. Depending on the application of the battery, the particle size of the electrochemically active material is preferably less than about 5 μm, more preferably less than about 1 μm. The active material contained in a given electrode can be selected based on the desired operating voltage and capacity and the intended function of the composite electrode as a cathode or anode in the final battery. Suitable electrochemically active materials are commercially available.
[0085] Low melting point electrolyte
[0086] The lower melting point (also referred to as melting temperature) inorganic solid electrolyte component preferably has a melting temperature of about 300°C to 850°C (673-973K), more preferably about 400°C to about 700°C. The low melting point solid inorganic electrolyte preferably comprises a doped metal oxide containing at least one of boron and carbon; the most preferred metal oxide is lithium oxide. The metal oxide may be doped with elements such as, but not limited to, silicon, fluorine, germanium or sulfur, or with compounds such as lithium fluoride, silicon dioxide, lithium metaborate or lithium orthoborate. When the electrolyte contains a dopant, its content is preferably from about 0.1 to about 20 atomic percent, more preferably from about 1 to about 20 atomic percent, even more preferably from about 5 to about 15 atomic percent, and most preferably from about 8 to about 12 atomic percent.
[0087] Suitable low melting point electrolytes include, for example, lithium metaborate, lithium orthoborate, lithium tetraborate, bulk LiPON, lithium fluoride-doped lithium metaborate, silicon-doped lithium tetraborate, lithium metaborate-doped lithium carbonate (LiBO2-Li2CO3), lithium orthoborate-doped lithium carbonate (Li3BO3-Li2CO3), lithium carbonate-doped lithium orthoborate (Li2CO3), lithium carbonate-doped lithium tetraborate (Li2CO3), lithium fluoride-doped lithium metaborate, lithium fluoride-doped lithium tetraborate, lithium fluoride-doped lithium carbonate (Li2CO3), lithium fluoride-doped lithium tetraborate ... 3- Li3BO3), silicon dioxide doped Li3BO3-Li2CO3 (SiO2-Li3BO3-Li2CO3) and lithium fluoride doped Li3BO3-Li2CO3 (LiF-Li3BO3-Li2CO3). The most preferred low melting point electrolytes include Li2CO3-Li3BO3 (referred to herein as "LBCO") and Li3BO3-Li2CO3 (referred to herein as "LCBO"), which have a melting temperature of 700°C. Amorphous or glass-ceramic lithium ion conductive inorganic electrolytes containing doped metal oxides containing boron and / or carbon (e.g., lithium carbonate doped with lithium orthoborate and lithium orthoborate doped with lithium carbonate) are preferred embodiments of the present invention, including those having the formula Li 9.3 C3BO 12.5 of electrolytes.
[0088] Other preferred materials include LCBFO (fluorine-doped LCBO), LCBSO (sulfur-doped LCBO), LBCSiO (silicon-doped LCBO), LBCSiFO (fluorine-doped LBCSiO) and LBCGeO (germanium-doped LCBO), as well as LBCSO (sulfur-doped LBCO), LCBSiO (silicon-doped LBCO), LCBSiFO (fluorine-doped LCBSiO) and LCBGeO (germanium-doped LBCO). Suitable low-melting electrolytes are commercially available or can be prepared by known methods.
[0089] In a preferred embodiment, the inorganic solid electrolyte has the general formula N v N′ w N″ x N″′ y N″″ z In the formula, N represents at least one element selected from Group IA of the periodic table, preferably Li, N′ represents at least one element selected from Group IVA of the periodic table, preferably carbon, N″ represents at least one element selected from Group IIIA of the periodic table, preferably boron, N″′ represents at least one element selected from Group VIA of the periodic table, preferably oxygen, and N″″ represents at least one dopant selected from Groups IA-VIIA of the periodic table and transition metals, preferably silicon, sulfur, germanium or fluorine.
[0090] In this formula, v, w, x, y and z are each zero or a positive number, including various combinations of integers and fractions or decimals. In a preferred embodiment, N, N', N", N"' and N"" represent lithium, carbon, boron, oxygen and silicon, respectively. In a second preferred embodiment, N, N', N" and N"' represent lithium, carbon, boron, oxygen and silicon, respectively, and z=0. In a preferred embodiment, the electrolyte contains carbon and / or boron and oxygen, and v, z, x, y and z are non-zero.
[0091] Exemplary lithium ion conductive electrolytes showing usable conductivity and good melting temperature characteristics are shown in Tables 1 and 2, but the low melting point electrolytes that can be used in the present invention are not limited to those listed. It is worth noting that the melting points of metal oxides are generally about 200 to 300°C higher than their corresponding glass transition temperatures. In addition, in the formulas of the materials in Table 1, except for oxygen, the components are listed in descending order of content in the material. That is, LCBO will contain more carbon than boron, and LBCO will contain more boron than carbon.
[0092] Table 1: Exemplary low melting temperature electrolytes
[0093]
[0094] *(LCBO is Li3BO3 doped Li2CO3), (LCBFO is F-doped LCBO), (LCBSO is S-doped LCBO), (LBCSiO is Si-doped LCBO), (LBCSiFO is F-doped LBCSiO) and (LBCGeO is Ge-doped LCBO).
[0095] Table 2: Exemplary low melting temperature electrolytes
[0096]
[0097] Although the exemplary electrolyte may have low ionic conductivity, its low melting temperature makes it suitable for effectively combining with lithium active battery materials and with other faster lithium ion conducting materials and forming low ionic impedance interfaces. Therefore, such low melting point materials can be heated to a molten or near-molten state and joined with lithium active materials without the interatomic migration problems typically associated with high temperature sintering, which until now has limited the practical construction of high-performance all-solid-state batteries. Such electrolytes are therefore included in electrodes to serve as binders or sintering aids for the active materials and other components of the electrodes. That is, the low melting temperature electrolyte acts as a glue that, when melted, flows between powder particles and establishes good contact. When solidified, the low melting point electrolyte is used to connect the particles together.
[0098] High ionic conductivity electrolyte
[0099] In addition to the electrochemically active material and the optional low melting temperature electrolyte, the composite electrode also includes a high ionic conductivity solid particulate inorganic electrolyte to promote faster ion transport throughout the cathode body. As previously mentioned, typical low melting point electrolytes do not have high ionic conductivity.
[0100] The term "high ionic conductivity" is understood to mean a conductivity greater than about 5×10 -5 S / cm. Exemplary high ionic conductivity solid electrolytes include LLTO (lithium lanthanum titanium oxide (Li 3x La 2 / 3-x TiO3 (x = 0.11)), LLZO (lithium lanthanum zirconium oxide (garnet, Li7La3Zr2O 12 )), LLBO (lithium lanthanum bismuth oxide) or similar solid-state, metal oxide-based electrolytes that exhibit high lithium ion conductivity. Lithium lanthanum zirconium oxide is preferred. The high ion conductivity electrolyte included in the composite electrode generally has a high melting point, which can be understood to mean a melting point greater than about 800°C (1073K).
[0101] The high melting point electrolyte is present in the form of large particles with diameters in the micrometer to nanometer range, more preferably in the micrometer range. More preferably, the diameter of the particles is from about 100 nanometers to about 1 millimeter, even more preferably from about 100 nanometers to about 100 micrometers, even more preferably from about 1 to about 100 micrometers, even more preferably from about 20 to about 50 micrometers, and most preferably from about 30 to about 50 micrometers. With large particles, as much active material in the electrode as possible can be in contact with the high melting point electrolyte.
[0102] Unlike the low melting point electrolyte that melts and refluxes, the high melting point electrolyte is retained in the electrode as discrete particles. The shape of the particles is not limited and can be cylindrical, spherical or other shapes. The cylindrical shape is preferred because it allows the electrode material to contact a larger surface area of the large electrolyte particles. If the particle size contains most of the electrolyte layer, such as about 60 to 80%, it is preferred. For example, a 50μm electrode layer will preferably contain an electrolyte with a particle size of about 40μm. Using such a relationship, due to the casting process used, the electrolyte particles will generally extend just onto the top surface of the electrode, where they contact the separator, thereby providing ionic conductivity from the electrode to the separator. In one embodiment, the cathode and anode are arranged on opposite sides of the separator, and the granular electrolyte particles contained in the cathode and / or anode extend into the separator.
[0103] Additional electrode components
[0104] The composite electrode may optionally contain up to about 5% by mass of an electronically conductive material to enhance the conduction of electrons. The term "electronically" or "electrically related" generally refers to the conduction of electrons rather than ions. Exemplary electronically conductive materials include, but are not limited to, cobalt oxide, carbon black, carbon nanotubes, silver, aluminum zinc oxide, doped silicon oxide, aluminum-doped zinc oxide, and the like. If present, this component provides low impedance for the transmission of electrons through the electrode to obtain high rate performance.
[0105] Preparation of composite electrodes
[0106] The composite electrode can be constructed as a separate wafer or particle, or can be manufactured as a thin coating applied to a substrate, such as a metal foil that can be used as a cathode current collector. For the purposes of this disclosure, the terms "wafer" and "particle" are not meant to be limiting and can refer to any desired shape or form.
[0107] The desired electrode structure can be formed using an additive manufacturing process such as three-dimensional (3D) printing, whereby the lithium active material and the electrolyte material are deposited in a predetermined pattern relative to each other. Without being limited by these embodiments, the desired patterning can be achieved using existing suitable 3-D printing techniques (including aerosol jet spraying, patterned slurry printing, or multilayer patterned casting and tape casting).
[0108] In the slurry method, the slurry is formed by mixing the cathode electrode material with a solvent and an optional organic polymer binder. Suitable binders are well known in the art and usually contain low molecular weight polymers, such as preferred polyvinyl butyral (PVB) and polyvinyl alcohol (PVA). The solvent can be any solvent in which the polymer is soluble, such as preferred ethanol and xylene. Then use a scraper technique, spin coating technique, spraying technique, printing technique or its equivalent technology that the resulting slurry (comprising composite cathode material, solvent and optional binder) is cast onto a non-stick substrate such as a polyester sheet. Then the coating is dried by evaporating the solvent. The solvent can evaporate by heating. The resulting strip casting can be removed from the casting surface.
[0109] Figure 2 Depicted is a casting surface 8 coated with a cathode layer 42, which can be applied using a conventional method of using a doctor blade to cast a slurry. The slurry contains active electrode materials and a highly conductive solid electrolyte, and may also include an electronic conductive additive and / or a low melting temperature electrolyte material as described above. In order to form the slurry, the components are preferably mixed together in a solvent in powder form to form a uniform distribution, preferably without a polymer binder. The resulting mixture is then doctor blade cast onto the casting surface. At this stage, the casting is preferably not yet removed from the casting surface.
[0110] Figure 3 The next step in the casting sequence for building a solid-state battery according to one embodiment of the present invention is depicted. A second slurry is prepared by mixing large electrolyte powder particles of a high conductivity electrolyte with a solvent and a low molecular weight polymer binder, such as preferably polyvinyl butyral (PVB) or polyvinyl alcohol (PVA). The solvent can be any solvent in which the polymer is soluble, such as the preferred xylene. These components are mixed to form a uniform distribution of large electrolyte particles throughout the mixture. The resulting mixture is then doctored on top of the previously cast cathode material 42. The binder and solvent of this second cast diffuse into the first cast layer. As the solvent evaporates, the binder bonds the two layers together. As Figure 3 As shown, this process results in relatively uniform arrangement and bonding of large electrolyte particles 40 to the surface of the original cathode casting 42 .
[0111] After the solvent evaporates, the resulting casting tape is lifted from the casting surface. The large electrolyte particles are then pressed into the surface of the first casting. The pressing process is preferably achieved by using a roller to press the casting tape. This process produces a Figure 4The cathode of the appearance shown in the figure, wherein the large electrolyte particles 44 are embedded in the cathode casting and exposed at the surface. In another method, the large electrolyte particles are cast first, followed by the active electrode material and binder as the top layer. In this way, once the solvent evaporates and the casting tape is lifted from the casting surface, the large electrolyte particles will be exposed on the bottom surface of the final cathode raw casting tape. The resulting casting tape is then calendered as described above.
[0112] The low melting temperature electrolyte (if present) also allows for coated current collector construction, whereby the electrode component slurry can be directly spin-coated, spray-coated, doctor blade cast, printed, etc. onto a low temperature metal current collector such as aluminum. However, it is also within the scope of the present invention to make the slurry without a low temperature electrolyte binder / sintering aid. The slurry can also be made without a polymer binder because it is supported by a metal foil, and it has been found that eliminating the polymer binder allows for the construction of a denser electrode.
[0113] In one embodiment, when the electrode is made without a low melting temperature electrolyte binder / sintering aid, the electrode is roll-calendered and then infiltrated with a low melting temperature electrolyte at a temperature of 400°C to 700°C as previously described.
[0114] In embodiments where the slurry includes a low melting temperature electrolyte, it is also calendered and sintered on the metal support surface at a temperature of 400° C. to 700° C. to reflux the electrolyte and form continuity. Optionally, as described below, the electrode may also be infiltrated with a low melting temperature electrolyte to further fill the pores and allow contact with all active materials. Electrodes according to embodiments of the present invention preferably have a thickness of about 3 microns to 1 millimeter.
[0115] It is also within the scope of the present invention to form an electrode or composite electrode directly on a current collector or other substrate using a melt quenching process. Such an electrode is formed by first depositing a low melting temperature electrolyte on the surface of a substrate in powder form or using a slurry of electrolyte powder and solvent. The solvent is evaporated, leaving a uniform distribution (coating) of electrolyte powder on top of the substrate, which is then melted or softened into a liquid phase (liquefaction). The substrate and the molten electrolyte are then quenched, preferably at room temperature, such as by using a roller to form a dense, defect-free electrode with a thickness in the range of about 3 microns to 1 mm on top of the substrate. Further within the scope of the present invention is the preparation of a free-standing electrode material (e.g., electrode particles) without a substrate, followed by a quenching process.
[0116] Quenching the electrolyte has the advantage of forming an amorphous or glass-ceramic material as an electrode (or composite electrode) that has a higher conductivity and a higher density relative to known materials. Although room temperature quenching is preferred, quenching at other temperatures below the melting point of the material is also within the scope of the present invention. Thus, melt quenching transforms the material from crystalline, with sharp, well-defined XRD (X-ray diffraction) peaks, to glass-ceramic (broad XRD peaks) or amorphous (no XRD peaks).
[0117] Cathode penetration
[0118] In one embodiment, a composite electrode is prepared by infiltrating a sintered porous electrode with a low melting point electrolyte, as described above, which acts as a binder to form a continuous path between high ion conductive electrolyte particles. This allows deeper and faster access to the cathode active material. In order to form such an electrode, a slurry of a low melting temperature electrolyte and a solvent such as isopropanol is cast on top of the already formed electrode. The evaporation of the solvent from the cast piece leaves a dry powder coating of the low melting point electrolyte on the cathode surface. Next, the cathode is heated to 400°C to 700°C (for example, in an oven) to reflux the low melting temperature electrolyte so that it migrates into the electrode under capillary forces. It is then cooled to form a solid electrolyte having a continuous path that runs through the depth of the electrode. The preferred electrolyte of this embodiment is Li3BO3-Li2CO3 with a melting temperature of 700°C.
[0119] When the electrode is coated on the current collector, the wetting process is the same as described above. The preferred electrolyte for infiltration of this embodiment is LiF-Li3BO3-Li2CO3, because its low melting point of 600°C allows the cathode to be coated on inexpensive aluminum foil.
[0120] Partition
[0121] The solid-state battery according to the present invention further comprises in a preferred embodiment a separator, most preferably an amorphous or glass-ceramic separator. Figure 5 A separator coating 48 is shown applied to the surface of cathode 42, which may be applied by magnetron sputtering deposition. Lithium phosphorus oxynitride, LiPON, is a preferred electrolyte material for application in thin film form by sputtering deposition. The separator thickness is preferably about 3 μm to 50 μm.
[0122] Another method is to use a powder electrolyte material to form a separator. In this method, a high melting point high ionic conductivity material (e.g., LAGP, LATP or preferably LLZO (preferably in nanopowder form)) with or without a sintering aid (e.g., a low melting temperature electrolyte) is mixed with a solvent and optionally an organic polymer binder to form a separator slurry as described above for the electrode slurry. The high melting point material is preferably in particle form and preferably has a particle size of about 100 nm to 1 mm as described above for the electrode.
[0123] Preferred low melting temperature electrolytes include doped metal oxides containing carbon and / or boron as described above with respect to the electrolyte contained in the electrode, and the above description also applies to the low melting temperature electrolyte contained in the separator. The most preferred sintering aid electrolyte is Li3BO3-Li2CO3 due to its low melting temperature (700°C) and high conductivity.
[0124] Suitable binders are well known in the art and typically contain low molecular weight polymers, such as preferred polyvinyl butyral (PVB) and polyvinyl alcohol (PVA). The solvent can be any solvent in which the polymer is soluble, such as preferred ethanol and xylene. If no polymer binder is used, many solvents are possible. When no polymer binder is used, isopropyl alcohol is most preferred.
[0125] The resulting separator slurry is then applied to the electrode surface using a doctor blade technique, spin coating technique, spray coating technique, printing technique, etc., which is pre-sintered or not pre-sintered at a temperature between 400 and 850°C, depending on the sintering aid. The coating is then dried by evaporating the solvent. Aerosol spraying or dry powder spraying using a carrier gas is also a suitable technique for applying the desired coating. The construction of the layered electrode / separator structure is completed by sintering in an oven at a temperature between 400 and 850°C, depending on the sintering aid as described above.
[0126] Alternatively, a slurry containing LLZO and an optional sintering aid electrolyte can be coated onto a separate casting surface and subsequently removed as a "green" tape. The resulting separator tape can then be laminated with a preformed cathode tape as previously described. The separator is laminated to the cathode surface with large electrolyte particles exposed. The cathode and separator tapes are laminated together and then calendered through a pair of compression rollers and then cut into individual discs or prismatic wafers of the desired cathode size. Subsequently, the cut is heated to about 400°C to burn out or evaporate the binder material. Finally, the cut is placed in an oven and sintered at a temperature as previously described.
[0127] Alternatively, raw LLZO powder can be densified by hot pressing to form a defect-free, 100% dense LLZO sheet. This sheet can be bonded to a sintered and infiltrated cathode using a binder such as, but not limited to, a low melting temperature electrolyte material as previously described.
[0128] Alternatively, the separator can be formed directly on the electrode using a melt quenching method as described above. Such a separator is formed by first depositing a low melting temperature electrolyte in powder form on the electrode surface or by using a slurry of electrolyte powder and solvent. The solvent evaporates, leaving a uniformly distributed electrolyte powder on the top of the electrode, which is then melted or softened into a liquid phase (liquefaction). The electrode and the molten electrolyte are then preferably quenched at room temperature, for example, by using a roller to form a dense, defect-free separator on the top of the electrode, with a thickness in the range of about 1 μm to 50 μm. The quenching electrolyte has the advantage of forming an amorphous or glass-ceramic material as a separator, which has a higher conductivity and a higher density relative to known materials. Although room temperature quenching is preferred, quenching at other temperatures below the melting point of the material is also within the scope of the present invention. Therefore, melt quenching changes the material from a crystalline, sharp, well-defined XRD peak to a glass-ceramic (broad XRD peak) or amorphous (no XRD peak).
[0129] It has been found that this method of melt-quenching materials from the melting point to a temperature sufficiently below the melting point makes amorphous or glass-ceramic materials have enhanced ionic conductivity. The melt-quenching method is preferably carried out by using a roller with 300rpm to 3000rpm, but more preferably about 700rpm speed roller quenching. As shown in Table 1, when melt-quenching forms glass-ceramics, the basic LCBO material has an electrical conductivity increase of about four times compared to the known crystalline form of the material. In addition, as shown in Table 1, when melt-quenching, the electrical conductivity of other materials also shows a significant increase of up to an order of magnitude. Therefore, relative to the electrical conductivity of the doped metal oxide powder before melt-quenching, the method of melt-quenching increases the electrical conductivity of the amorphous or glass-ceramic doped metal oxide obtained by at least about three times, even at least about five times.
[0130] Table 1 further shows that the sulfur-doped base LCBO shows increased conductivity and a lower melting point to 600°C. This lower melting point makes the material more easily glass-forming upon quenching and improves processability with less reactive battery components. Similarly, melt-quenched fluorine-doped LBCSiO has a significantly lower melting point (from 800°C to 660°C) with only a slight decrease in conductivity, thus making the material more compatible with active materials used in cathodes due to fewer parasitic reactions at these high temperatures.
[0131] In one embodiment, the low melting temperature electrolyte in the electrode is LCBO, and the low melting temperature electrolyte in the separator is lithium fluoride doped LCBO, Li6C2BFO8, which has a melting temperature of 600°C, 100°C lower than the melting temperature of the non-doped material. This difference in melting temperature between LCBO and Li6C2BFO8 enables the construction of an electrode that promotes ionic conduction inside the electrode while being unaffected by the lower melting temperature process of applying a coating of Li6C2BFO8 to the electrode surface as a separator. That is, because the temperature required to melt the electrolyte in the separator is lower, the electrolyte in the electrode is not affected (does not melt).
[0132] In another embodiment, the electrolyte powder applied to the electrode surface can be a second low melting temperature electrolyte material, as opposed to a sintered separator coating. Instead of a sintered separator, the coated electrode is heated to the melting temperature of the coating to produce a liquid film. The separator film is formed when the liquid cools and resolidifies. In this embodiment, the low melting temperature electrolyte can also be applied using a spin coating technique while in a molten state. The electrolyte can be any of the low melting temperature electrolytes described previously, and most preferably Li3BO3-Li2CO3.
[0133] Solid-state batteries
[0134] The primary or secondary solid-state battery according to the present invention comprises a composite electrode, a counter electrode and a separator as described above. For example, if the composite electrode is a composite cathode, a conventional anode, such as lithium metal, lithium alloy metal or lithium alloy precursor, can be used. The separator can be as described above, and the metal anode can be applied to the separator by physical or vapor deposition (e.g., by sputtering or thermal evaporation) under vacuum. Alternatively, the battery can be completed by applying a metal foil or coating, for example, copper on the electrolyte surface opposite to the cathode to form a lithium-free battery. In this case, lithium is plated between the foil and the electrolyte to form an anode during initial charging.
[0135] As previously described, the anode can also be a composite electrode. In one embodiment, the anode is cast onto an electrolyte-coated cathode so that the battery has a lithium-ion battery structure, wherein the first composite electrode is formed using a lithium ion insertion compound such as lithium titanium oxide (LTO) with a low lithium reaction potential. As previously described, a composite separator is formed using a low melting temperature glass electrolyte binder and a filling material. A second composite electrode is formed using a lithium insertion material having a higher reaction potential than the material used in the first electrode, such as lithium nickel cobalt manganese oxide (NCM). The first composite electrode material can be used as an anode and the second composite electrode can be used as a cathode. The anode, separator, and cathode materials are stacked to form an integral structure having a separator located between the anode and the cathode. The stacked components can be heat treated at a temperature ranging from 400°C to 700°C. Subsequently, the anode, electrolyte, and cathode multilayer structure are heated at a temperature sufficient to sinter the structure together, or in the case of a low melting temperature adhesive electrolyte, at a temperature sufficient to reflux the electrolyte and combine the component electrodes and separators together.
[0136] Preferably, the melting temperature of the separator layer is lower than the melting temperature of the low melting temperature binder electrolyte used in the cathode.The heat treatment will only melt the low melting temperature electrolyte used in the separator so that it binds all the layers in the stack together.
[0137] Figure 6 A cross-sectional view of a battery according to an embodiment of the present invention is shown. Electrolyte particles 54 extend the separator layer 46 into the cathode 42. Calculations 47 give a geometric impression of the effect of the increased surface area of the separator. Although each particle is different and has a random shape, they are approximated as spherical for analytical convenience. The top of the particle is embedded as part of the separator. For further convenience, it is assumed that the depth to which lithium ions 52 can effectively diffuse in and out of the cathode active material is 15 μm, and the distance 43 from the center of the large electrolyte particle to this depth where lithium can effectively diffuse is 45 microns. Therefore, for an average electrolyte particle size of 30 μm at radius 41 and an active material thickness of 75 μm, the accessible net volume of active cathode material per particle can be approximated as 268,606 μm 3 , minus the volume cut off by the separator interface at the top surface of the cathode. This is significantly larger than the 121,500 μm that diffuses 15 μm into the cathode through the flat interface with the electrolyte. 3 .
[0138] Figure 7 A 3D image showing the structure surrounding the electrolyte particle. If the particle is assumed to be able to completely close the closed cubic volume, the net volume of cathode material that is close will be 615,903 μm 3 , minus the volume of active material displaced by the separator, and minus the volume cut off by the separator interface at the top surface of the cathode.
[0139] The present invention will now be further illustrated in the following non-limiting examples.
[0140] Example 1: Preparation and analysis of solid electrolyte
[0141] The high conductivity electrolyte LLZO (lithium lanthanum zirconium oxide (garnet, Li7La3Zr2O 12 )). 3.8 g of LiOH, 10 g of La2O3, 6 g of ZrO, 0.27 g of Al and 1.12 g of TaO were ground in THF. All components were obtained from commercial sources. The resulting mixture was dried under vacuum and then heated at 715°C for 1 hour and 900°C for 3 hours. The resulting powder was pressed into pellets in a Carver press and subsequently sintered at 1200°C in oxygen. Thus, the sintered pellets were taken out of the furnace and ground into powder to provide the desired LLZO.
[0142] LLZO impedance measurement is shown in Figure 8a and 8b middle. Figure 8a The graph in represents the entire measurement spectrum, and Figure 8b The graph in Figure 2 focuses on the high frequency part. Based on these data, the estimated ionic conductivity of LLZO is 5×10 -4 S / cm. Large LLZO particles were obtained by hot pressing LLZO powder at 1200°C to sinter and form a dense structure. The dense particles were then crushed into fine particles and separated using sieves of various ranges to obtain particles between 25 μm and 45 μm.
[0143] A LiO2O3 having a melting temperature of 700°C and a formula of LiO2O3 was prepared by the following solid-state reaction 9.3 C3BO 12.5 The low melting temperature electrolyte Li3BO3:Li2CO3, lithium carbonate doped with lithium orthoborate. Li3BO3 was prepared by mixing 24.1 g of Li2O2 with 14.7 g of lithium tetraborate, both obtained from Sigma Aldrich. The powder was ground in 35 ml of THF for 8 hours. The resulting powder was dried on a hot plate at 80°C for 3 hours and then dried in a vacuum oven at 120°C for 22 hours. The powder so dried was placed in a tube furnace and heated at 580°C for 10 hours under an oxygen flow to form the precursor of the desired lithium orthoborate powder.
[0144] To form Li3BO3:Li2CO3, lithium orthoborate precursor powder and lithium carbonate (Alfa Aeser product number 554-13-2) were mixed in a ratio of 1:2.76 weight percent and then hot pressed at 700°C to form a dense composite electrolyte. An alternative to hot pressing the mixture to form a composite electrolyte is to heat it to its melting point to form a homogeneous molten mixture. After cooling, the resulting material was ground into a powder with a particle size of less than 3 μm.
[0145] Alternatively, to lower the melting point of Li3BO3:Li2CO3, it can be doped with lithium fluoride (LiF) at 1:1:2.76 wt% (LiF:Li3BO3:Li2CO3). The precursors are then melted into a homogeneous mixture to form a composite electrolyte upon cooling.
[0146] The conductivity of the particles was measured before grinding into the final powder. Platinum was sputtered on both sides of the particles to provide electrical contacts. Impedance measurements were performed using a Solartron 1260 instrument. The impedance spectra of hot pressed and melted boron-doped lithium carbonate particles (Li3BO3:Li2CO3) and melted LiF-doped Li3BO3:Li2CO3 are shown in Figure 2. Fig. 9 As shown. This figure represents the spectrum of the entire measurement. Based on the impedance data, the ionic conductivity of hot pressed Li3BO3:Li2CO3, molten Li3BO3:Li2CO3 and molten LiF doped Li3BO3:Li2CO3 particles at room temperature was estimated to be 1.1x10-6S / cm, 9.5x10-7S / cm and 6.0x10-7S / cm, respectively.
[0147] Example 2: Preparation of a battery using an NCM cathode and a low melting temperature electrolyte
[0148] A mixture was prepared by high energy grinding of 4 g (61%) NCM active cathode material powder, (36 wt%) 2.4 g nano-sized (<0.3 μm average particle size) LLZO electrolyte (prepared in Example 1) and 0.2 g (3 wt%) polymer binder (PVB) with 1.5 ml ethanol and 1.5 ml xylene solvent. The mixture was then cast onto a non-stick polyester sheet and allowed to dry. Multiple cast pieces were made and then calendered together to form a single multilayer sheet, each layer about 50 μm thick. Discs were punched out of the sheet and then heated at 400°C for 3 hours to remove the binder and then heated at 850°C for 30 minutes to obtain a porous sintered cathode disc.
[0149] After sintering, a low melting temperature electrolyte slurry was cast onto one surface of the cathode disk. The slurry was formed by mixing 0.2 g of Li3BO3:Li2CO3 (prepared in Example 1) with 2 g of isopropyl alcohol solvent (IPA). The solvent was evaporated from the cast piece leaving a dry powder coating of Li3BO3:Li2CO3 on the cathode surface. Next, the cathode was placed in an oven at 700°C to reflux the Li3BO3:Li2CO3, allowing it to migrate into the cathode under capillary forces.
[0150] The now solid electrolyte infiltrated cathode was then coated with LiPON (commercially available from Kurt Lesker) by sputter deposition to form the separator. The cell was completed by evaporating a lithium seed layer onto the surface of the LiPON to form the anode.
[0151] The battery was tested and the charge / discharge cycle data and impedance spectrum were shown in Fig.10 and 11 . Fig.10 The charge / discharge cycle data in show that the battery has a discharge capacity of 400 μAh. The battery was tested at room temperature at C / 100. Fig.11 The corresponding EIS spectrum in shows that the impedance of the battery without large LLZO particles is about 2200 ohms.
[0152] Example 3: Preparation of a battery with NCM cathode, low melting temperature electrolyte and high surface area separator interface
[0153] A mixture was prepared by high energy grinding of 4 g (61%) NCM active cathode material powder, (36 wt%) 2.4 g nano-sized (<0.3 μm average particle size) LLZO electrolyte (prepared in Example 1) and 0.2 g (3 wt%) polymer binder (PVB) with 1.5 ml ethanol and 1.5 ml xylene solvent. The mixture was cast onto a non-stick polyester sheet and allowed to dry. The multi-layer castings were calendered together into a single sheet so that the particles were more evenly distributed, and each layer was about 100 μm thick before calendering.
[0154] The LLZO separator was prepared by mixing a ratio of 2g / 2g (50 / 50 wt%) of nano LLZO powder (approximately 25 nanometers) with large particle LLZO powder (25 microns to 45 microns) with 0.28 grams of 7 wt% polymer binder (PVB), 1.6ml ethanol and 1.6ml xylene solvent. The resulting slurry was doctor blade cast onto a non-stick surface as described above and allowed to dry. The resulting film was removed from the casting surface and paired with a multilayer cathode plate and calendered together. The cast piece was calendered using a steel roller. The calendering process densifies the electrolyte layer so that the particles therein are closer to each other. Similarly, the NCM particles in the cathode below the cathode layer are squeezed closer to each other, thereby increasing the particle density of the cathode. The final thickness of the cathode is 80μm, which results in large LLZO electrolyte particles extending a significant distance from the surface to the depth of the cathode. Since the diameter of the large particles in the separator is greater than the thickness of the separator, the larger particles eventually protrude into the cathode layer, thereby providing increased interface roughness and a less tortuous conductive path into the cathode.
[0155] The disks were punched out of the plates and then heated at 400°C to remove the binder and then heated at 850°C for 1 hour to obtain porous sintered cathode disks with large particles of separator material embedded and exposed on their surfaces.
[0156] After sintering, a low melting temperature electrolyte slurry was cast onto one surface of the cathode disk. The slurry was formed by mixing 0.2 g of Li3BO3:Li2CO3 (Example 1) with 2 g of isopropanol solvent. The solvent evaporated from the cast leaving a dry powder coating of Li3BO3:Li2CO3 on the cathode surface. Next, the cathode was placed in an oven at 700°C to reflux the Li3BO3:Li2CO3, allowing it to migrate into the cathode under capillary forces.
[0157] Subsequently, a LiPON separator material with a thickness of about 2.5 microns was deposited on the smooth side of the thin particles by RF magnetron sputtering. The electrolyte coating directly contacts the exposed large LLZO particles embedded in the cathode surface. Finally, a Li metal anode was deposited on the LiPON by thermal evaporation in vacuum. The resulting cells were tested and impedance spectroscopy was run using a Solartron and charge / discharge cycling data was obtained using a Maccor battery cycler to generate Fig.11 and 12 Data shown. Fig.11 It was shown that cells with large LLZO particles embedded in the cathode and in intimate contact with the LiPON separator had lower impedance (approximately 1000 ohms lower) than cells without large particles. Fig.12The charge and discharge capacities of the battery with large LLZO particles were also significantly enhanced compared to the battery without large LLZO particles. The theoretical capacities of the two batteries based on the active material content were roughly the same. Each battery was tested at the same C rate (C / 100) at room temperature.
[0158] Example 4: Use of NCM with LLZO electrolyte (nano-sized and / or large particle size) with and without Li3BO3-Li2CO3 Sintering aids for cathode preparation
[0159] (a) Cathode prepared using only NCM and nanosized (<0.3 μm average particle size) LLZO electrolyte
[0160] A mixture was prepared by high energy grinding of 4 g (49%) NCM active cathode material powder, (49 wt%) 4 g nanoscale (<0.3 μm average particle size) LLZO electrolyte and 0.2 g (2 wt%) polymer binder (PVB) with 4 g ethanol and 4 g xylene solvents.
[0161] (b) Preparation of cathodes using NCM with nanosized (<0.3 μm average particle size) and large (25 μm to 45 μm average particle size) LLZO electrolytes
[0162] A mixture was prepared by high energy grinding of 4 g (52%) NCM active cathode material powder, (46 wt%) 3.5 g nanoscale (<0.3 μm average particle size) LLZO electrolyte and 0.2 g (2 wt%) polymer binder (PVB) with 4 g ethanol and 4 g xylene solvents.
[0163] (c) Preparation of cathodes using NCM, nanosized (<0.3 μm average particle size), large (25 μm to 45 μm average particle size) LLZO electrolytes, and low melting temperature electrolytes as sintering aids
[0164] A mixture was prepared by high energy grinding of 4 g (50 wt%) NCM active cathode material powder, (44 wt%) 3.5 g nano-sized (<0.3 μm average particle size) LLZO electrolyte, (3 wt%) 0.25 g Li3BO3:Li2CO3 sintering aid and 0.2 g (3 wt%) polymer binder (PVB) with 4 g ethanol and 4 g xylene solvents.
[0165] Cathode mixtures a, b and c were cast separately onto non-stick polyester sheets and dried. The cast pieces in green form were removed from the substrate stack and calendered together to form a single multilayer sheet, each approximately 30 μm thick. Discs were punched out of the sheets and then heated at 400°C for 3 hours to remove the binder. Subsequently, the cathode samples from Examples a and b were sintered at 850°C for 30 minutes, while Example 4c was sintered at 700°C for 30 minutes to obtain porous sintered cathode discs. The Li3BO3-Li2CO3 sintering aid in Example 4c allowed the cathode to be fully sintered at 700°C, 150°C lower than the sintering temperature of Examples 4a and b without a binder. The lower sintering temperature reduces parasitic reactions between the NCM active material and the LLZO electrolyte, thereby improving charge transfer.
[0166] After sintering, a low melting temperature electrolyte slurry was cast onto one surface of each cathode disc. The slurry was formed by mixing 0.2 g of Li3BO3:Li2CO3 with 2 g of isopropanol solvent. The solvent evaporated from the cast piece leaving a dry powder coating of Li3BO3:Li2CO3 on the cathode surface. Next, the cathode was placed in an oven at 700°C to reflux the Li3BO3:Li2CO3, allowing it to migrate into the cathode under capillary forces.
[0167] The cathode, now infiltrated with the solid electrolyte, is then coated with LiPON by sputter deposition to form the separator. The cell is completed by evaporating a lithium seed layer onto the surface of the LiPON to form the anode.
[0168] Fig.13 The charge and discharge capacities of the cells from Examples 4a, 4b, and 4c when cycled at a C rate of C / 15 at room temperature are shown. As can be seen, the cathode with only nanoscale LLZO (Example 4a) exhibits a capacity of 0.20 mAh / cm 2 The discharge capacity of the cathode with nano-sized and large-sized LLZO showed a significant improvement in average voltage and discharge capacity, with an increase of about 140% (0.48 mAh / cm 2 When the sintering aid Li3BO3-Li2CO3 was added to the nano-sized and large-particle LLZO, a further improvement in the average voltage and discharge capacity was obtained (increased by 25% to 0.60 mAh / cm 2 ).
[0169] Example 5: Preparation of separator by melt quenching
[0170] A mixture was prepared by high energy grinding of 4 g (61%) NCM active cathode material powder, (36 wt%) 2.4 g nano-sized (<0.3 μm average particle size) LLZO electrolyte and 0.2 g (3 wt%) polymer binder (PVB) with 1.5 ml ethanol and 1.5 ml xylene solvent. The mixture was then cast onto a non-stick polyester sheet and allowed to dry. Multiple cast pieces were made and then calendered together to form a single multilayer sheet, each layer about 50 μm thick. Discs were punched out of the sheet and then heated at 400°C for 3 hours to remove the binder and then heated at 850°C for 30 minutes to obtain a porous sintered cathode disc.
[0171] After sintering the cathode disc, 0.1 g of dry powder of Li3BO3:Li2CO3:Li2SO4 was suspended in isopropanol and then placed on top of the porous cathode disc. Next, the cathode was placed in an oven at 620°C to melt the Li3BO3:Li2CO3:Li2SO4, allowing it to migrate into the cathode under capillary forces until the voids in the cathode were filled, leaving excess molten material on the surface of the cathode disc. The filled cathode disc with Li3BO3:Li2CO3:Li2SO4 on its surface was then rolled using a roller at room temperature, thereby quenching the electrolyte on the cathode surface and inside, forming a glass separator on the cathode surface, which also extends through the thickness of the cathode.
[0172] Those skilled in the art will appreciate that changes may be made to the above embodiments without departing from the broad inventive concept thereof. Therefore, it should be understood that the present invention is not limited to the specific embodiments disclosed, but is intended to cover modifications within the spirit and scope of the present invention as defined by the appended claims.
Claims
1. An amorphous or glass-ceramic lithium ion conducting inorganic electrolyte, wherein: The electrolyte includes lithium carbonate doped with lithium orthoborate and at least one dopant selected from the group consisting of lithium fluoride, silicon dioxide, fluorine, sulfur, silicon, and germanium.
2. An amorphous or glass-ceramic lithium ion conducting inorganic electrolyte, wherein: The electrolyte includes lithium orthoborate doped with lithium carbonate and at least one dopant selected from the group consisting of lithium fluoride, silicon dioxide, fluorine, sulfur, silicon, and germanium.
3. An amorphous or glass-ceramic lithium ion conducting inorganic electrolyte, wherein: The electrolyte comprises lithium carbonate doped with lithium orthoborate, and the electrolyte has a chemical formula Li 9.3 C3BO 12.5 .
4. A method of making an amorphous or glass-ceramic inorganic electrolyte comprising a doped metal oxide containing at least one of carbon and boron, the method comprising forming a coating of a powder of the doped metal oxide on a substrate, heating the coated substrate to liquefy the powder, and quenching the coated substrate at a temperature below the melting point of the powder to form the amorphous or glass-ceramic electrolyte; wherein, The electrolyte comprises lithium carbonate doped with lithium orthoborate and at least one dopant selected from the group consisting of lithium fluoride, silicon dioxide, fluorine, sulfur, silicon and germanium, or the electrolyte comprises lithium orthoborate doped with lithium carbonate and at least one dopant selected from the group consisting of lithium fluoride, silicon dioxide, fluorine, sulfur, silicon and germanium.
5. The method according to claim 4, wherein: The amorphous or glass-ceramic electrolyte has an electrical conductivity at least three times higher than that of the powder of the doped metal oxide.
6. The method according to claim 4, wherein: The amorphous or glass-ceramic electrolyte has an electrical conductivity at least five times higher than the electrical conductivity of the powder of the doped metal oxide.
Citation Information
Patent Citations
Lithium ion-transmissible glass ceramics and battery and gas sensor using it
JP1998097811A
Ion conductive solid, method for producing the same, and solid-state battery
JP2015013775A